2018
DOI: 10.1096/fj.201701127r
|View full text |Cite
|
Sign up to set email alerts
|

Methionine oxidized apolipoprotein A‐I at the crossroads of HDL biogenesis and amyloid formation

Abstract: Apolipoprotein A-I (apoA-I) shares with other exchangeable apolipoproteins a high level of structural plasticity. In the lipid-free state, the apolipoprotein amphipathic α-helices interact intra- and intermolecularly, providing structural stabilization by self-association. We have reported that lipid-free apoA-I becomes amyloidogenic upon physiologically relevant (myeloperoxidase-mediated) Met oxidation. In this study, we established that Met oxidation promotes amyloidogenesis by reducing the stability of apoA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 115 publications
(244 reference statements)
4
24
0
Order By: Relevance
“…35) could also facilitate the interaction of apoA-I with macrophages (35) and induce their pro-inflammatory response, as shown in the present study.…”
Section: Pro-inflammatory Effect Of Apoa-i With Oxidized Methioninessupporting
confidence: 70%
See 3 more Smart Citations
“…35) could also facilitate the interaction of apoA-I with macrophages (35) and induce their pro-inflammatory response, as shown in the present study.…”
Section: Pro-inflammatory Effect Of Apoa-i With Oxidized Methioninessupporting
confidence: 70%
“…In this study, we investigated how oxidation of methionine to methionine sulfoxide (Met(O)) imparts pro-inflammatory properties to lipid-free apoA-I. For our experiments, we used a reproducible and well-characterized oxidized human plasma apoA-I (Met(O)-ApoA-I), in which all three methionine residues are oxidized to Met(O) by an excess of H 2 O 2 (34,35,44).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…37,38 Met oxidation of apoAI directly impairs its function, including inhibition of two critical early events in RCT: sterol export by ABCA1 and activation of LCAT 39 ; and reduces the stability, resulting in amyloid formation. 40 Recently, clinical studies have reported a significant increase in Met oxidation of apoAI in patients with CAD and human heterozygote carriers of SR-BI mutation. 38,41 However, the absence of highly specific antibody has impeded the direct detection of MetSO sites in apoAI in this study.…”
Section: Discussionmentioning
confidence: 99%